2016
DOI: 10.1080/08964289.2016.1154003
|View full text |Cite
|
Sign up to set email alerts
|

Using the Bem and Klein Grid Scores to Predict Health Services Usage by Men

Abstract: We examined the association between scores on the Bem Sex Roles Inventory (BSRI), Klein Sexual Orientation Grid (KSOG) and utilization of hospital inpatient services, emergency departments, and outpatient clinic visits in the past 12 months among 53 men (mean age 39 years). The femininity subscale score on the BSRI, ever having had gonorrhea and age were the three variables identified in a multivariate linear regression significantly predicting use of total health services. This supports the hypothesis that se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Five of the 6 items were adopted from the Sexual Orientation Grid created by Klein et al, 23 which has been widely utilized in several studies. 24 , 25 The remaining item (affection) was newly included in this questionnaire. Although the original grid by Klein et al assesses sexual orientation in the past and present and as an ideal, we analyzed sexual orientation only at the present.…”
Section: Methodsmentioning
confidence: 99%
“…Five of the 6 items were adopted from the Sexual Orientation Grid created by Klein et al, 23 which has been widely utilized in several studies. 24 , 25 The remaining item (affection) was newly included in this questionnaire. Although the original grid by Klein et al assesses sexual orientation in the past and present and as an ideal, we analyzed sexual orientation only at the present.…”
Section: Methodsmentioning
confidence: 99%
“…Reynolds and colleagues’ paper highlights how even among a population of low income men, many of whom are homeless, being gay or bisexual still exacerbates men’s health risks and is associated with fewer outpatient visits than their heterosexual counterparts. 29 Cook and Calebs’ paper explores how the social stressors and stigma associated with sexual minority status can have deleterious effects on attachment, social connectivity and social support across the lifecourse. 30 Bauermeister and colleagues exploration of the sexual behaviors of young men who have sex with men again suggests that the intersection of multiple dimensions of vulnerability – living in lower socioeconomic disadvantaged neighborhoods, having fewer economic resources and having less stable housing – are linked to the need of these men commodifying their bodies for shelter, food or to fulfill other basic needs.…”
Section: Context Of Men’s Health Disparities Researchmentioning
confidence: 99%
“…Previously published research on health services utilization among men may be determined by both insurance and noninsurance related characteristics (Edwards et al, 2007; Reynolds et al, 2016; Storholm et al, 2010). A qualitative study using semistructured interviews of men and women aged 18–64 identified both barriers and enablers of obtaining preventive care.…”
mentioning
confidence: 99%